Efficacy of different in-office treatments for dentin hypersensitivity: randomized and parallel clinical trial - Ramos, Fernanda de Souza e Silva [UNESP] (2024)
The aim of this clinical, prospective, randomized, and parallel study was to evaluate different in-office treatments for dentin hypersensitivity (DH). One hundred ninety-two teeth with non-cavitated root exposures were treated using different desensitizers: fluoride varnish (Duraphat – FLU); bioactive ceramic solution (Biosilicate-BIOS); universal self-etching adhesive (Single Bond Universal – SBU); bioactive photoactivated varnish (PRG filler-SPRG). The degree of DH was analyzed using a visual analog scale (VAS) and computerized visual scale (CoVAS), before treatments and after 7, 15, and 30 days from the first session. Comparisons among desensitizers were performed using the Kruskal-Wallis and Dunn's tests. Friedman test was used to compare between times (p ≤ 0.05). Comparing desensitizers FLU presented a higher value of DH than BIOS using VAS at 7 days, however, no differences were found using CoVAS analysis. Comparing times, BIOS and SBU showed a reduction in DH after 7 days and SBU showed a reduction at 30 days compared to 7 days using VAS. FLU and SPRG groups reduced DH from 15 days to 30 days using VAS. There was a reduction in DH for FLU, BIOS, and SBU after 7 days and for BIOS this reduction also occurred at 30 days when compared to 15 days using CoVAS. SPRG group showed a reduction from 15 to 30 days. All desensitizers tested were able to reduce the initial sensitivity. The bioactive ceramic solution reduced the DH gradually after 30 days using computerized analysis.